Vibration Properties of a Steel-PMMA Composite Beam - Yuyang He; Xiaoxiong Jin (Shock and Vibration)
A steel-polymethyl methacrylate (steel-PMMA) beam was fabricated to investigate the vibration properties of a one-dimensional phononic crystal structure. The experimental system included an excitation system, a signal acquisition system, and a data analysis and processing system. When an excitation signal was exerted on one end of the beam, the signals of six response points were collected with acceleration sensors. Subsequent signal analysis showed that the beam was attenuated in certain frequency ranges. The lumped mass method was then used to calculate the bandgap of the phononic crystal beam to analyze the vibration properties of a beam made of two different materials. The finite element method was also employed to simulate the vibration of the phononic crystal beam, and the simulation results were consistent with theoretical calculations. The existence of the bandgap was confirmed experimentally and theoretically, which allows for the potential applications of phononic crystals, including wave guiding and filtering, in integrated structures.